Unbridling the Economic Growth and Environmental Nexus in Pakistan - Kayani, Umar Nawaz; Mumtaz, Roohi; Fahlevi, Mochammad; Nasseredine , Hassan; Hadinata , Acep (International Journal of Energy Economics and Policy, 2024)
The Kuznets Curve framework is used in this study to examine the complex relationship between economic growth and environmental impact in Pakistan. The study employs descriptive statistics, pairwise correlations, and regression analysis to uncover intricate relationships among crucial variables such as pollution, environmental performance, GDP, income, and taxation. The results underscore the complex trade-offs and non-linear connections that exist within these relationships, underscoring the importance of informed policy choices in order to attain sustainable development that effectively reconciles economic advancement and environmental preservation within the specific context of Pakistan.